Video clip transfer of radiological images using a mobile telephone in emergency neurosurgical consultations (3G multi-media messaging service) - Ganesan, D.; Waran, V.; Bahuri, N.F.; Narayanan, V.; Kadir, K.A. (2012)
Background The purpose of this study was to validate and assess the accuracy and usefulness of sending short video clips in 3gp file format of an entire scan series of patients using mobile telephones running on 3G-MMS technology, to enable consultation between junior doctors in a neurosurgical unit and the consultants on call after office hours.